PHILOSOPHICAL BACKGROUND OF INTERRELIGIOUS CONFLICTS AND THEIR RESOLUTION: . - Furtado, Vincent Gabriel (Journal of Dharma, 1998)
The persons with whom we have to deal have not merely a different way of thinking and feeling, a different conviction and attitude, but also a different perception of the world, a different recognition and order of meaning, a different touch from the regions of existence, a different faith, a different soil. To affirm all this in the midst of the hard situations of conflict without relaxing their real seriousness is the way by which we may .be permitted to touch on the other's truth or untruth, justice or injustice.